2005
DOI: 10.2337/diacare.28.3.527
|View full text |Cite
|
Sign up to set email alerts
|

Dosage Effects of Diabetes Self-Management Education for Mexican Americans

Abstract: OBJECTIVE -The objective of this study was to compare two diabetes self-management interventions designed for Mexican Americans: "extended" (24 h of education, 28 h of support groups) and "compressed" (16 h of education, 6 h of support groups). Both interventions were culturally competent regarding language, diet, social emphasis, family participation, and incorporating cultural beliefs.RESEARCH DESIGN AND METHODS -We recruited 216 persons between 35 and 70 years of age diagnosed with type 2 diabetes Ն1 year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
213
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(224 citation statements)
references
References 16 publications
10
213
1
Order By: Relevance
“…12 In this study, a larger impact of the group visit program may have been observed had a greater proportion of patients participating in the group visit program attended more sessions. Only 46% of those who participated in the program attended at least three of the four sessions.…”
Section: Discussionmentioning
confidence: 71%
“…12 In this study, a larger impact of the group visit program may have been observed had a greater proportion of patients participating in the group visit program attended more sessions. Only 46% of those who participated in the program attended at least three of the four sessions.…”
Section: Discussionmentioning
confidence: 71%
“…[10][11][12][13] In brief, the setting was Starr County, one of 14 Texas counties delimited in part by the Rio Grande River and bordering Northern Mexico; 98% of Starr County residents are Mexican American, and 35% of these are foreign born. 14 The County has been designated by the State of Texas as a Health Professional Shortage and Medically Underserved Area, with lower ratios of physicians and nurses to the population than the rest of the State.…”
Section: Methodsmentioning
confidence: 99%
“…12,13,16 Our previous data from Starr County showed that regular monitoring of blood glucose levels resulted in greater improvements in glycemic control. Because of downloading and data importing challenges of previous glucometer models, we do not have complete, parallel monitoring data from our previous studies, so direct comparisons across studies are not possible.…”
Section: Monitoring Rates In Previous Starr County Studiesmentioning
confidence: 99%
See 2 more Smart Citations